2016
DOI: 10.1007/s11695-016-2326-6
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Syndrome as a Cause of False Acute Abdomen in the Early Postoperative Period After Bariatric Surgery–a Report of Two Cases

Abstract: Takotsubo syndrome, also known as broken-heart syndrome, stress-induced cardiomyopathy or transient apical ballooning syndrome, is a transient disorder characterized by segmental left ventricular failure in the absence of obstructive coronary artery disease. Most cases of Takotsubo syndrome are caused by acute stress that leads to a sudden, temporary weakening of the cardiac musculature. This stress triggers a rise in circulating catecholamine levels that results in acute ventricular dysfunction. In this repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Tori et al reported TC developing after cholecystectomy for gallstones and common bile stones ( 12 , 16 , 17 ). Viegas et al reported two cases of TC in the “early” postoperative period after bariatric surgery ( 15 ). We believe that thiamine deficient for being noncompliant with long-term postoperative care may have contributed to her cardiac condition, which entertains the possibility of patients having wet beriberi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tori et al reported TC developing after cholecystectomy for gallstones and common bile stones ( 12 , 16 , 17 ). Viegas et al reported two cases of TC in the “early” postoperative period after bariatric surgery ( 15 ). We believe that thiamine deficient for being noncompliant with long-term postoperative care may have contributed to her cardiac condition, which entertains the possibility of patients having wet beriberi.…”
Section: Discussionmentioning
confidence: 99%
“…Also, biliary pancreatitis has been complicated by TC, and TC may develop following laparoscopic cholecystectomy ( 13 , 14 ). The development of TC is also documented following gastric bypass surgery ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…What also remains unknown is the significance of nutrition disorders in the aetiology and the course of stress cardiomyopathy. Takotsubo syndrome is diagnosed not only in people with low body mass, as there are known cases of people suffering from anorexia, but also in obese patients [18][19][20]. On average, obese patients with TS constitute between 10-20% of the whole group [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The PubMed was employed from its inception to 9/6/22 in response to MeHS “obesity and takotsubo” and 29 articles were accessed [ 2 , 3 , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]; in addition, a recently published article with reference to morbid obesity [ 36 ] was included, for a total of 30 articles. A meta-analysis could not be performed, since many of the accessed articles ( Table 1 ) did not comprise granular (individual patient-based) information on obesity.…”
Section: Methodsmentioning
confidence: 99%
“… 10. [ 18 ] A report of 40-year old woman with HTN and obesity (BMI of 43.28 kg/m 2 ) who suffered TTS 105 days after BS, and following laparoscopic surgery for a subphrenic abscess resulting from the BS, who also received dopamine and NE; also, a report of a 31-year old woman with HTN and obesity (BMI 38.28 kg/m 2 ) who developed TTS in the immediate postoperative period following BS. 11.…”
Section: Methodsmentioning
confidence: 99%